Sejarah Pertumbuhan Fiqh Pada Masa Rasulullah, Sahabat, Hingga Kontemporer - Ahmad Mu'is, Sainawi; Muhammad Fahmi Wahyudianto; Sela Safira; Mungalimatul Munyarida (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2024)
The development of fiqh at the time of the Prophet Muhammad was the initial stage in the formation of Islamic law which became the main basis of sharia. In this period, the main sources of law consisted of the Qur'an and the Sunnah of the Prophet. Fiqh developed through direct responses to problems faced by Muslims, with the Prophet as the leader who gave legal decisions based on revelation and ijtihad. The decisions of the Prophet covered various aspects of life, such as worship, muamalah, and social interaction. The process of delivering the law was carried out in stages, taking into account the social, cultural and readiness context of the community. This approach made fiqh at that time dynamic and solutive, adapted to the conditions of Arab society at that time. Research on the development of fiqh during the Prophet's era provides deep insight into the basic principles of Islamic law that are adaptable, fair, and oriented towards the welfare of the people.